2018
DOI: 10.12669/pjms.345.14817
|View full text |Cite
|
Sign up to set email alerts
|

Role of topical antibiotics in prophylaxis against endophthalmitis following intravitreal antibiotics

Abstract: Objective:To compare the prophylactic use of antibiotic with placebo to prevent post intra-vitreal endophthalmitis and other complications.Methods:A prospective, cohort study was conducted at Ophthalmology Department, Fauji Foundation Hospital (FFH), from June 2016 to July 2017. A total of 1082 eyes of 673 patients were enrolled in this study. Patients were selected at non-random and divided into two groups. In Group-I, non – exposed, placebo eye drops were given after intravitreal bevacizumab injections and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Doctors would like to believe these perioperative managements might decrease the pathogens. However, some published articles showed that using antibiotics eye drops could not make the infection rate lower 2,3 . Some study showed that local antibiotic eye drops might increase microbial resistance and opportunistic infection 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Doctors would like to believe these perioperative managements might decrease the pathogens. However, some published articles showed that using antibiotics eye drops could not make the infection rate lower 2,3 . Some study showed that local antibiotic eye drops might increase microbial resistance and opportunistic infection 4 .…”
Section: Introductionmentioning
confidence: 99%